EXPERIMENTAL STUDY OF POROUS CONCRETE WITH VARIOUS ADDITON OF RICE HUSK ASH - Tonapa, Suryanti Rapang; Sandy, Desi; Febriani, Lisa (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
Focus from this study is porous concrete. To improve the mechanic properties’s porous concrete, one of which is with addition of fiber. The Fiber material used in this study is ash of rice husk. Dimension’s for cylinder sample is 15 x 30 cm, as much 84 samples with addition of fiber 0%, 0.5%, 1% and 1.5% from weight of cement. Result of porous concrete testing, with addition of fiber showed the largest pore volume is 22.081%. While porous concrete without addition of fiber, the largest percentage of pore volume is 23.533%. Weight of volume with addition fiber, the largest percentage is 1894.737 kg/m3 and without addition fiber is 1963.883 kg/m3. Value of compressive strength testing with addition fiber is 13.48 MPa and split tensile strength is obtained 1.94 MPa, while value of compressive strength without addition fiber is 12.03 MPa and split tensile strength is obtained 1.77 MPa. Value of flexural testing and modulus elastic of porous concrete with addition of fiber, respectively the value’s 1.946 MPa and 342.85 MPa, while value of flexural testing and modulus elasticity of porous concrete without addition of fiber, respectively the value’s 1.58 MPa and 360 MPa.